HEALING FOREST DEVELOPMENT DESIGN IN TAMAN HUTAN KAMPUS, IPB DARMAGA BOGOR - Putri Nabila; Rachmad Hermawan; Ervizal A.M. Zuhud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2023)
Cities are centers of economic activity that can attact people to seek livelihoods, thus causing an increase in urbanization and an increase in population density. High population density in urban areas will mainly have an impact on individual stress levels. The steps involved in designing a landscape are inventory, data analysis, ideas and concepts, and the design process. Accessibility to Taman Hutan Kampus is relatively easy because of the position of Taman Hutan Kampus which is directly adjacent to the main road. The average of LAI value is 0,480-1,548 which belongs to the low canopy density. Respondents showed a positive response to Taman Hutan Kampus as healing forest. The design is made to accommodate spaces that create activities based on the needs of visitors, namely induction area, active area, and therapy area. Activities that can be done to support healing activities are enjoying the beauty of nature by walking, speaking positively, using all the sense to feel tree textures, and relaxing the mind.